Plan comunicacional para el posicionamiento del turismo en la represa Baba, recinto el descanso, del cantón Buena Fe, año 2015. Quevedo - Goyes Marcillo, Hilda Ysabel (2015)
The present work for a Communicative plan for positioning of tourism in Baba Dam, enclosure Rest, industry "Duckbill" Canton Buena Fe, aims to help the positioning of tourism in the area, revealing the potential tourism in the world, in the first chapter, the contextual framework of the research through the problem statement, formulation of objectives, the route of the hypothesis and justification of the research is detailed. The second chapter describes the theoretical basis of the relevant theory related to Baba dam and tourism through the theoretical, conceptual and legal foundations are developed. In chapter three consist methods, types, and techniques, sources of information, the reference population to investigate and their respective shows. In the fourth chapter the results of the investigation are presented through a market survey, which served to know the opinion of the people about the importance of turning this place into a tourist center and through these results we proceeded to the developing a proposal, which states among other socio-economic aspects, features the Tourism Management and Marketing Project Market, Mission, Vision and Communication Plan. Finally, conclusions and recommendations are presented....